Early expression of osteopontin glycoprotein on the ocular surface and in tear fluid contributes to ocular surface diseases in type 2 diabetic mice. - Ananya Datta; Xin Yi Li; Manshul Nagpaul (PLoS ONE)
Purpose Osteopontin (OPN) is a glycosylated, secreted phosphoprotein known to be elevated in both human and mouse retinas during various stages of diabetic retinopathy. However, its specific roles in modulating ocular surface dynamics and immune responses in diabetes remain unexplored. This study aims to investigate the role of OPN in the development of ocular surface disease (OSD) in type 2 diabetic (T2D) mice. Methods Three- to four-week-old C57BL/6 wild-type (WT) and OPN-knockout (OPN-/-) mice were fed a high-fat diet (HFD) and were rendered diabetic by streptozotocin (STZ; 40 mg/kg body weight) in citrate buffer (vehicle); non-diabetic controls were injected with vehicle alone. Diabetes was confirmed if blood glucose levels were >200 mg/dL, measured 1-2 weeks post-STZ injection. Control, age- and sex-matched db/db diabetic mice fed a standard chow diet were also included in this study. Ocular surface inflammation was assessed using ELISA to quantify inflammatory cytokine proteins and wheat germ agglutinin (WGA) staining was utilized to highlight corneal surface irregularities. Clinical signs were evaluated by corneal fluorescein staining, tear production measurements, and tear sodium (Na+) concentration assessments. These evaluations were conducted 4, 6, 8 and 16-weeks post-diabetes onset in WT and OPN-/- mice and were compared to those obtained in non-diabetic controls. Statistical analysis was performed using a two-way ANOVA, with significance set at P < 0.05. Results Both WT and OPN-/- mice developed T2D within 4 and 8 weeks, respectively, following HFD + STZ treatment. Corneal OPN levels in WT diabetic mice increased ~2-fold at 2 weeks and ~4-fold at 16 weeks compared to non-diabetic controls, with similar elevations observed in their tear fluid. Diabetic db/db mice also exhibited elevated OPN levels in the blood and ocular surface, which persisted as diabetes progressed. Enhanced fluorescein staining, indicating corneal irregularities, appeared in WT mice at 8 weeks and in OPN-/- mice at 10 weeks post-T2D induction. Additionally, WGA staining showed a significant reduction in fluorescence intensity in WT mice treated with HFD and STZ, confirming corneal surface irregularities that were delayed in OPN-/- mice. Elevated tear sodium concentration was observed in both WT and OPN-/- diabetic mice without affecting tear production rates. Notably, OPN levels increased early, at week 2, following HFD and STZ treatment, preceding changes in interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and matrix metalloproteinase-9 (MMP-9). Upregulation of IL-6 became apparent at 6 weeks in WT mice and was delayed until 10 weeks in OPN-/- mice post-T2D induction. Conclusions Elevated OPN levels were detected early post-T2D induction in diabetic WT and db/db mice corneas without initial subclinical changes. This early increase in OPN precedes other proinflammatory cytokines associated with eventual ocular surface inflammation as diabetes progresses. Persistence of OPN also correlated with clinical signs such as increased corneal surface irregularities and elevated tear Na+ concentration. Future research will explore OPN's role as a biomarker in ocular surface disease (OSD), including dry eye disease (DED), and investigate its impact on inflammatory processes and other mechanistic pathways in diabetic ocular complications.